Poetic Critique Encounters with Art and Literature - Chaouli, Michel; Lietz, Jan; Müller-Tamm, Jutta; Schleusener, Simon (WeltLiteraturen / World Literatures, 2021)
This book seeks to breathe new life into Friedrich Schlegel's idea of 'poetic critique,' but also asks about its limitations. What forms might critique take when practiced poetically? Can this practice be rigorous enough to maintain a right of citizenship in the academy? How can the notion of poetic critique intervene in current debates on critique and post-critique? These essays offer a variety of new perspectives on these and similar questions.